A critical evaluation of DC microgrid implementation in Indonesia: opportunities and challenges - Levin Halim; Pinto Anugrah; Aditya Kurniawan; Khairuddin Karim (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This study thoroughly investigates the potential of direct current (DC) microgrids to enhance electricity access in rural and remote areas of Indonesia that continue to face significant obstacles despite ongoing national electrification efforts. Utilizing a mixed-methods approach, this research comprehensively evaluates socio-economic and technical factors that influence the adoption of DC microgrids. The results indicate that DC microgrids offer significant potential for enhancing energy access, reliability, and sustainability, particularly when combined with renewable energy sources. This aligns with Indonesia’s move towards renewable energy. Nevertheless, the analysis identifies significant obstacles, such as the substantial initial investment, the requirement for complete regulatory frameworks, and the technological complexities that need to be conquered. In conclusion, DC microgrids present a promising solution for rural electrification. However, the implementation requires a strategy that emphasizes strategic investments, policy innovation, and capacity-building initiatives. This research significantly contributes to the study of sustainable energy by evaluating the criticality of integrating policies and technology for implementing DC microgrids as a key factor in achieving sustainable energy access in Indonesia.